2017
DOI: 10.3389/fpsyg.2017.01928
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Orientation Patterns toward Emotional Faces and Temperamental Correlates of Preschool Oppositional Defiant Problems: The Moderating Role of Callous-Unemotional Traits and Anxiety Symptoms

Abstract: The present study examined the independent contributions and the interaction effects of oppositional defiant problems (ODD), callous unemotional traits (CU) and anxiety symptoms on attentional orienting to emotional faces, in a community sample of preschoolers. Additionally, based on Rothbart's (2007) model of temperament, we analyzed whether fine-grained dimensions of reactivity (fear, anger, discomfort, sadness, activity level, approach, high intensity pleasure, impulsivity) and self-regulation (attentional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Table S1 in Supplementary Materials provides an overview of the 52 studies published from 2015 to 2020, included in the review for analysis. Among the 52 studies, most authors reported results on more than one dimension of the model, e.g., [ 69 , 70 ], 47 reported effects on mental health, e.g., [ 71 , 72 , 73 ] or on neurobiological features, e.g., [ 69 , 74 , 75 ], 22 on social contexts, e.g., [ 36 , 76 ], eight on social adjustment, e.g., [ 77 , 78 ], 10 on social roles and social interactions, e.g., [ 79 , 80 ] and 19 on executive functions or cognition, e.g., [ 81 , 82 ]. The majority (k = 17) were carried out in the USA, e.g., [ 83 , 84 ], two in Canada [ 70 , 85 ], two in Australia, two in Israel, the one in Europe (Spain, Germany, Netherlands, etc.).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table S1 in Supplementary Materials provides an overview of the 52 studies published from 2015 to 2020, included in the review for analysis. Among the 52 studies, most authors reported results on more than one dimension of the model, e.g., [ 69 , 70 ], 47 reported effects on mental health, e.g., [ 71 , 72 , 73 ] or on neurobiological features, e.g., [ 69 , 74 , 75 ], 22 on social contexts, e.g., [ 36 , 76 ], eight on social adjustment, e.g., [ 77 , 78 ], 10 on social roles and social interactions, e.g., [ 79 , 80 ] and 19 on executive functions or cognition, e.g., [ 81 , 82 ]. The majority (k = 17) were carried out in the USA, e.g., [ 83 , 84 ], two in Canada [ 70 , 85 ], two in Australia, two in Israel, the one in Europe (Spain, Germany, Netherlands, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Among many different tools (see note to Table S2 ), measures of behavioral and emotional symptomatology in children and adolescents (e.g., CD, ODD, ADHD, anxiety, depression) have been mainly assessed using the SDQ (e.g., [ 4 , 79 ]), the CBCL (e.g., [ 72 , 94 ]) the Kiddie-Schedule for Affective Disorders and Schizophrenia (K-SADS-PL; [ 95 ]), e.g., [ 96 , 97 ] and the Reactive-Proactive Aggression Questionnaire (RPQ; [ 98 ]), e.g., [ 69 , 99 ]. To measure the presence of autistic traits in children and adolescents, different scales have been used, as the Social Responsiveness Scale (SRS; [ 100 ]), e.g., [ 101 ] and the Social Communication Questionnaire (SCQ; [ 102 ]), e.g., [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations